Implementasi Model Pembelajaran BCCT (Beyond Centers And Circle Times) dan Model Pembelajaran Konsiderasi di TK Khalifah Baciro Kota Yogyakarta - Raudatul Hasanah; Muhammad Abdul Latif (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
This study aims to provide an overview of the implementation of the BCCT learning model and the consideration learning model in TK Khalifah Baciro, Yogyakarta City. This research method uses qualitative research. The subjects of this research were 4 class teachers, 1 school principal and 36 students. Data collection uses observation, interviews, and documentation. The data analysis uses the Huberman Milles Model. The authenticity test uses triangulation of techniques and sources. The results showed that the BCCT learning model and consideration can be used as a reference for early childhood education institutions as an effort to develop aspects of creative and innovative child development. In addition, considerations of the learning model can shape the character of the child's mercy, such as manners, good character and good behavior.